Symbiotic efficiency of Rhizobium leguminosarum sv. trifolii strains originating from the subpolar and temperate climate regions - Monika Janczarek; Marta Kozieł; Paulina Adamczyk; Katarzyna Buczek; Michał Kalita; Anna Gromada; Aleksandra Mordzińska-Rak; Cezary Polakowski; Andrzej Bieganowski (Scientific Reports, 2024)
Abstract Red clover (Trifolium pratense L.) is a forage legume cultivated worldwide. This plant is capable of establishing a nitrogen-fixing symbiosis with Rhizobium leguminosarum symbiovar trifolii strains. To date, no comparative analysis of the symbiotic properties and heterogeneity of T. pratense microsymbionts derived from two distinct geographic regions has been performed. In this study, the symbiotic properties of strains originating from the subpolar and temperate climate zones in a wide range of temperatures (10–25 °C) have been characterized. Our results indicate that all the studied T. pratense microsymbionts from two geographic regions were highly efficient in host plant nodulation and nitrogen fixation in a wide range of temperatures. However, some differences between the populations and between the strains within the individual population examined were observed. Based on the nodC and nifH sequences, the symbiotic diversity of the strains was estimated. In general, 13 alleles for nodC and for nifH were identified. Moreover, 21 and 61 polymorphic sites in the nodC and nifH sequences were found, respectively, indicating that the latter gene shows higher heterogeneity than the former one. Among the nodC and nifH alleles, three genotypes (I–III) were the most frequent, whereas the other alleles (IV–XIII) proved to be unique for the individual strains. Based on the nodC and nifH allele types, 20 nodC-nifH genotypes were identified. Among them, the most frequent were three genotypes marked as A (6 strains), B (5 strains), and C (3 strains). Type A was exclusively found in the temperate strains, whereas types B and C were identified in the subpolar strains. The remaining 17 genotypes were found in single strains. In conclusion, our data indicate that R. leguminosarum sv. trifolii strains derived from two climatic zones show a high diversity with respect to the symbiotic efficiency and heterogeneity. However, some of the R. leguminosarum sv. trifolii strains exhibit very good symbiotic potential in the wide range of the temperatures tested; hence, they may be used in the future for improvement of legume crop production.